2013
DOI: 10.3748/wjg.v19.i28.4464
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant properties of glutamine and its role in VEGF-Akt pathways in portal hypertension gastropathy

Abstract: Glutamine treatment demonstrated to reduce oxidative damage but does not reduce angiogenesis induced by PH in gastric tissue, demonstrating a beneficial role for the PI3K-Akt-eNOS pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 50 publications
1
15
0
1
Order By: Relevance
“…This increase was of 476% (24h) and 646% (48h) in relation to control groups, while Vitamin E-supplemented groups showed a reduction of 36.2% (24h) and 29.8% (48h) as compared to groups receiving TAA, which in a way can be explained by the improvement of the hepatic parenchyma. Similar findings were reported by other authors who assessed nitric oxide levels (7,22) .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This increase was of 476% (24h) and 646% (48h) in relation to control groups, while Vitamin E-supplemented groups showed a reduction of 36.2% (24h) and 29.8% (48h) as compared to groups receiving TAA, which in a way can be explained by the improvement of the hepatic parenchyma. Similar findings were reported by other authors who assessed nitric oxide levels (7,22) .…”
Section: Discussionsupporting
confidence: 92%
“…In a study investigating the preventive effect of quercetin in animals with TAA-induced SALF, de Oliveira et al, showed significantly increased SOD activity from the administration of the flavonoid. Other works have reported decreased SOD activity from the administration of other antioxidants (8,22,23) .…”
Section: Discussionmentioning
confidence: 81%
“…Blockage of VEGF promoted portal pressure reduction [31,32], and the inhibition of JAK2/STAT3 signalling by AG490 greatly decreased the expression of VEGF and phospho-eNOS, which contributed to the inhibition of angiogenesis and the increase of the splanchnic vascular tone. Thus, in splanchnic circulation, the decreased formation of blood vessels and increased SMAR may have decreased SMABF.…”
Section: Discussionmentioning
confidence: 98%
“…Gly present in the purified peptide is known to be a direct proton donor which is critical to the free radical scavenging property of antioxidant peptides due to their capacity to reduce unpaired electrons or free radicals by donating protons (Qian et al 2008). Glutamine was shown to act as a potent antioxidant that protected the gastric mucosa and decreased oxidative damage to the gastric mucosa in a rat model of portal hypertension (Marques et al 2013). Arginine supplementation enhanced antioxidant defence in experimental rats (Shan et al 2013).…”
Section: Purification Of Uf Fraction Using Semi-preparative Rp-hplcmentioning
confidence: 97%